2016
DOI: 10.1002/aenm.201600457
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Perovskite Solar Cells: Progresses and Perspectives

Abstract: During the past 6 years, perovskite solar cells have experienced a rapid development and shown great potential as the next‐generation photovoltaics. For the perovskite solar cells with regular structure (n‐i‐p structure), device efficiency has reached over 20% after the intense efforts of researchers from all over the world. Recently, perovskite solar cells with the inverted structure (p‐i‐n structure) have been becoming more and more attractive, owing to their easy‐fabrication, cost‐effectiveness, and suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
384
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 426 publications
(390 citation statements)
references
References 149 publications
(472 reference statements)
4
384
0
2
Order By: Relevance
“…[13] The planar p-i-n PVSCs have many advantages over their competitors, such as simple device fabrication, high stability, and negligible hysteresis effect. [14] The rapid development in this area has now made it necessary to review the current state of the art for planar p-i-n PVSCs by focusing on their special structures, materials, and interfaces, in order to inform and promote future research efforts.…”
mentioning
confidence: 99%
“…[13] The planar p-i-n PVSCs have many advantages over their competitors, such as simple device fabrication, high stability, and negligible hysteresis effect. [14] The rapid development in this area has now made it necessary to review the current state of the art for planar p-i-n PVSCs by focusing on their special structures, materials, and interfaces, in order to inform and promote future research efforts.…”
mentioning
confidence: 99%
“…[1][2][3][4] The performance of PSCs can be significantly limited by charge carrier recombination, due to the unbalanced charge carrier transport in the device. [5,6] Some effective strategies have been carried out to improve the charge carrier balance, such as:…”
mentioning
confidence: 99%
“…Similarly, reports have shown that by incorporating an ultra-thin P3TMAHT intercalating layer in the device structure for efficient hole extraction, the average PCE was improved from 8.52% to 11.28% [82]. Dedicated reviews on interfacial engineering of perovskite solar cells can be found in the literature [72][73][74]. Some of the notable materials employed in PSC device fabrication are shown in Figure 8.…”
Section: Charge Selective Contacts and Interfacesmentioning
confidence: 95%
“…The n -i-p is also called as normal device structure and p-i-n structure is also called as inverted device structure. Simply, depending on the position of the ETM and HTM, the device structure varies [70,[72][73][74]. The details about the different electron and hole transporting layers are discussed in the forthcoming section.…”
Section: Perovskite Solar Cell Device Architecturesmentioning
confidence: 99%